Resveratrol alleviates heat stress-induced impairment of intestinal morphology, microflora, and barrier integrity in broilers - Zhang, C; Zhao, X H; Yang, L; Chen, X Y; Jiang, R S; Jin, S H; Geng, Z Y (Poultry science, 2017)
Abstract This study was to investigate the effect of resveratrol on intestinal morphology, microfloras, and barrier integrity of broilers subjected to heat stress. Two-hundred-seventy 21-day-old Cobb male broilers were randomly allocated to 3 treatment groups, each of which included 6 replicates with 15 birds per replicate. The 3 treatment groups were as follows: the control group, in which birds were exposed to thermoneutral condition (22 ± 1°C), and the heat stress group and heat stress + resveratrol (400 mg/kg) group, in which birds were exposed to cyclic heat stress (33 ± 1°C for 10 h/d from 0800 to 1800 h and 22 ± 1°C for the remaining time. Compared with birds in the control group, birds in the heat stress group exhibited decreased (P < 0.05) final body weight, average daily gain, average daily feed intake, villus height, villus height to crypt depth ratio, goblet cells numbers, populations of Lactobacillus and Bifidobacterium, and mRNA levels of mucin-2, claudin-1, occludin, zona occludens-1, and E-cadherin, and increased (P < 0.05) crypt depth, serum D-lactic acid and fluorescein isothiocyanate dextran contents and diamine oxidase activity, and populations of Salmonella, Escherichia coli, and Clostridium. Compared with birds in the heat stress group, birds in the heat stress + resveratrol group exhibited decreased (P < 0.05) crypt depth, serum D-lactic acid and fluorescein isothiocyanate dextran contents, and populations of Escherichia coli, and increased (P < 0.05) final body weight, villus height, villus height to crypt depth ratio, goblet cells numbers, populations of Lactobacillus and Bifidobacterium, and mRNA levels of mucin-2, claudin-1, occludin, and E-cadherin. Taken together, these results indicated for the first time that dietary addition of resveratrol was effective in partially ameliorating the adverse effects of heat stress on intestinal barrier function in broilers by restoring the impaired villus-crypt structure, modifying the profiles of intestinal microfloras, and altering the mRNA expression of intestinal tight junctions- and adherence junctions-related genes.